Numerical Research on Mitigating Soil Frost Heave Around Gas Pipelines by Utilizing Heat Pipes to Transfer Shallow Geothermal Energy - Peng Xu; Yuyang Bai (Energies, 2025)
Frost heave in seasonally frozen soil surrounding natural gas pipelines (NGPs) can cause severe damage to adjacent infrastructure, including road surfaces and buildings. Based on the stratigraphic characteristics of seasonal frozen soil in Beijing, a soil–natural gas pipeline–heat pipe heat transfer model was developed to investigate the mitigation effect of the soil-freezing phenomenon by transferring shallow geothermal energy utilizing heat pipes. Results reveal that heat pipe configurations (distance, inclination angle, etc.) significantly affect soil temperature distribution and the soil frost heave mitigation effect. When the distance between the heat pipe wall and the NGP wall reaches 200 mm, or when the inclined angle between the heat pipe axis and the model centerline is 15°, the soil temperature above the NGP increases by 9.7 K and 17.7 K, respectively, demonstrating effective mitigation of the soil frost heave problem. In the range of 2500–40,000 W/(m·K), the thermal conductivity of heat pipes substantially impacts heat transfer efficiency, but the efficiency improvement plateaus beyond 20,000 W/(m·K). Furthermore, adding fins to the heat pipe condensation sections elevates local soil temperature peaks above the NGP to 274.2 K, which is 5.5 K higher than that without fins, indicating enhanced heat transfer performance. These findings show that utilizing heat pipes to transfer shallow geothermal energy can significantly raise soil temperatures above the NGP and effectively mitigate the soil frost heave problem, providing theoretical support for the practical applications of heat pipes in soil frost heave management.